Consistency of gender differences in bullying in cross-cultural surveys. (March 2019) - Smith, Peter K.; López-Castro, Leticia; Robinson, Susanne; Görzig, Anke
Abstract: Many studies have reported on gender differences in bully and victim rates, but with the majority of reports from a small number of countries. Here we report on such gender differences from five large cross-national data bases. We report on overall male:female (M:F) ratios, and variations in these by age (or grade), by survey time point, and by offline/online bullying. We also compare consistency of M:F ratios across countries, over the five surveys. The preponderance of male perpetrators of bullying is found consistently across surveys, and survey time point. It is also consistent by age, but HBSC data suggest a curvilinear trend in early adolescence. Males also tend to more frequently be victims of bullying, consistent across age and survey time point, but with variations by survey. There is some indication of a decrease in M:F ratio recently in mid-adolescence, possibly related to online bullying. At least relatively, females are more involved as victims of online than offline bullying. Comparing recent findings on M:F ratio across countries for the five surveys, correlations vary from high to near zero. Implications for the explanation of gender differences in different countries, the comparability of data from different surveys, and for gender-specific interventions, are discussed. Highlights: Males are consistently more frequently perpetrators of bullying, but this male preponderance is reduced in early adolescence. Males tend to more frequently be victims of bullying, but with variations by survey. The male preponderance in being a victim of bullying may be decreasing recently in mid-adolescence. At least relatively, females are more involved as victims of online than offline bullying. Variations by country in male:female ratios of being a victim are considerable.